Tunable Synthesis of Ultrathin BiOCl 2D Nanosheets for Efficient Photocatalytic Degradation of Carbamazepine upon Visible-Light Irradiation - Shuo Xu; Xiaoya Gao; Wenfeng Xu; Pengfei Jin; Yongmei Kuang (Journal of Chemistry)
A series of ultrathin BiOCl 2D nanosheet photocatalysts were prepared by the TBAOH-assisted hydrolysis method in water. The effects of tetrabutylammonium hydroxide (TBAOH) dosages, chlorine source, preparation pH value, ultrasonic treatment, and magnetic stirring on the photocatalytic degradation dynamics of carbamazepine were examined under visible-light irradiation to optimize the preparation parameters. It was found that ultrathin BiOCl prepared with TBAOH dosages of 1 mmol and chlorine source of NaCl in the pH of 2 upon magnetic stirring of 6 h displayed the highest photocatalytic degradation rate constant (0.0038 min−1) of carbamazepine, which is 7.6 times higher than that with the ordinary BiOCl (without TBAOH). To clarify the mechanism on the outstanding photocatalytic activity of ultrathin BiOCl, the elemental composition/state, micromorphology, and separation efficiency of photogenerated electron-hole pairs were investigated by X-ray photoelectron spectroscopy (XPS), scanning electron microscope (SEM), and photoluminescence (PL). Results showed that the presence of oxygen vacancy, ultrathin nanosheet structure, and improved separation efficiency of photogenerated electron-hole pairs contributed to the excellent photocatalytic degradation activity of ultrathin BiOCl. The obtained result provides a novel method to fabricate ultrathin BiOCl with excellent photocatalytic degradation activity of carbamazepine under visible-light irradiation.